Pengaruh Model Project Based Learning (PjBL) Berbasis Drama Budaya Jawa terhadap Kemampuan Komunikasi Peserta Didik Kelas IV SD Negeri 01 Karang Tahun Pelajaran 2025/2026 - Latifah Fadlilah Ristanti; Oktiana Handini; Dite Hastini (Lembaga Pengembangan Kinerja Dosen, 2025)
This research was conducted on fourth-grade students of SD Negeri 01 Karang with the aim of analyzing the effect of the implementation of the Javanese culture-based Project Based Learning (PjBL) model on students' communication skills in the 2025/2026 academic year. The research subjects were 25 students, consisting of 12 male students and 13 female students. This type of research is quantitative with a One Group Pre-Test Post-Test Design. The research procedure began with the administration of a pre-research questionnaire to determine the level of instrument validity, and the results of the validity test showed that there were 10 questionnaire items that met the valid criteria for use in data collection. Data analysis was carried out through a normality test using the One-Sample Shapiro-Wilk formula and a hypothesis test using the Paired Sample T-Test formula. The results of the analysis showed a significance value <0.000 with a probability <0.05, so it can be concluded that the research hypothesis is proven, namely there is a significant effect of the implementation of the Javanese culture-based PjBL model on improving the communication skills of fourth-grade students. These findings confirm that project-based learning linked to local cultural contexts not only improves communication skills but also helps students better understand and appreciate their local cultural values. Thus, cultural integration in the PjBL model is an effective strategy for improving the quality of learning, both academically and strengthening students' cultural identities.